Transpiration in Quercus suber trees under shallow water table conditions: the role of soil and groundwater (Hydrological Processes, 2013)
Water is one of the major environmental factors limiting plant growth and survival in the Mediterranean region. Quercus suber L. woodlands occupy vast areas in the Iberian Peninsula, frequently under shallow water table conditions. The relative magnitude of soil and groundwater uptake to supply transpiration is not easy to evaluate under these circumstances. We recently developed a conceptual framework for the functioning of the root system in Q. suber that simulates well tree transpiration, based on two types of root behaviour: shallow connected and deep connected. Although this significantly improved knowledge on the functional traits of Mediterranean Q. suber, the approach has the limitation of requiring root sap flow data, which are seldom available. In this work, we present alternative methodologies to assess if trees are connected to groundwater and to estimate the soil and groundwater contributions to tree transpiration. We provide evidence on the tree unrestricted access to groundwater solely based on meteorological, stem sap flow and leaf water potential data. Using a soil mass balance approach, we estimated the yearly soil and groundwater contributions to tree transpiration: 69.7% and 30.3%, respectively. Groundwater uptake became dominant in the dry summer: 73.2% of tree transpiration. Results reproduce extremely well those derived from root modelling. Because of its simplicity both in formulation and data requirements, our approach is potentially liable to be adapted to other groundwater- dependent Mediterranean oak sites, where interactions between land use and water resources may be relevant.